2018
DOI: 10.1108/gkmc-12-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and adoption of mobile technologies in the delivery of services in academic libraries in Jordan

Abstract: Purpose Mobile technologies (MT) have been attracting the attention of academic library stakeholders for some time, as it is considered a strong communication channel that can offer advanced library services. Furthermore, MT can offer a number of flexible options for library users. Accordingly, the overarching aim of this research is to investigate the potentials of implementing MT within academic libraries in public universities in Jordan from library staff viewpoint. Exploring library staff expectation of MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Again, 71.9% of the respondents said "Yes" to the assertion that lack of requisite skills on the part of library staff might obstruct the successful deployment of m-techs for the delivery of library service. These results resonate with the findings of Ghuloum and Ahmed (2011) and Hamad et al (2018) that library staff of academic libraries quite often do not possess the right kind of ICT skills needed for the smooth deployment of emerging technologies.…”
Section: Challenges Associated With the Provision Of Library Services Through Mobile Technologysupporting
confidence: 89%
“…Again, 71.9% of the respondents said "Yes" to the assertion that lack of requisite skills on the part of library staff might obstruct the successful deployment of m-techs for the delivery of library service. These results resonate with the findings of Ghuloum and Ahmed (2011) and Hamad et al (2018) that library staff of academic libraries quite often do not possess the right kind of ICT skills needed for the smooth deployment of emerging technologies.…”
Section: Challenges Associated With the Provision Of Library Services Through Mobile Technologysupporting
confidence: 89%
“…In a similar study, Abdul Rahman, Mohezar, Habidin and Mohduzi (2020) identified the CFSs of the continued usage of DL, such as the user-driven implementation, institutional support, training and education, the DL milieu and communication support, a continuation of usage intention, net benefits and user satisfaction. While the study mentioned above was conducted in the military context, Wang et al (2018aWang et al ( , 2018b, Yip et al (2021) and Hamad et al (2018) conducted their studies in educational settings. However, the studies mentioned above share a common denominator in that they concur on the impact of socio-economic and technological factors as critical determinants of the successful adaptation of DLs.…”
Section: Mobile Digital Librariesmentioning
confidence: 99%
“…This concept has equally relieved the academic libraries from spending extract funds on purchasing of computers for internet access or for online public access catalogues (OPAC) access. Hamad et al (2018) support the concept and say that libraries have started using phone applications to either access books or for OPAC services. currently developing digital libraries that are meant to assist library users to access digital content.…”
Section: Emerging Trends Of Academic Librariesmentioning
confidence: 99%